Transcriptome Profile Analysis of Arabidopsis Reveals the Drought Stress-Induced Long Non-coding RNAs Associated With Photosynthesis, Chlorophyll Synthesis, Fatty Acid Synthesis and Degradation - Chen, Kang; Huang, Yang; Liu, Chunni; Liang, Yu; Li, Maoteng (Frontiers in Plant Science, 2021)
Background: Long non-coding RNAs (lncRNAs) play an important role in the response of plants to drought stress. The previous studies have reported that overexpression of LEA3 and VOC could enhance drought tolerance and improve the oil content in Brassica napus and Arabidopsis thaliana, and most of the efforts have been invested in the gene function analysis, there is little understanding of how genes that involved in these important pathways are regulated. Results: In the present study, the transcriptomic results of LEA3 and VOC over-expressed (OE) lines were compared with the RNAi lines, mutant lines and control lines under long-term and short-term drought treatment, a series of differentially expressed lncRNAs were identified, and their regulation patterns in mRNA were also investigated in above mentioned materials. The regulation of the target genes of differentially expressed lncRNAs on plant biological functions was studied. It was revealed that the mutant lines had less drought-response related lncRNAs than that of the OE lines. Functional analysis demonstrated that multiple genes were involved in the carbon-fixing and chlorophyll metabolism, such as CDR1, CHLM, and CH1, were regulated by the upregulated lncRNA in OE lines. In LEA-OE, AT4G13180 that promotes the fatty acid synthesis was regulated by five lncRNAs that were upregulated under both long-term and short-term drought treatments. The key genes, including of SHM1, GOX2 and GS2, in the methylglyoxal synthesis pathway were all regulated by a number of down-regulated lncRNAs in OE lines, thereby reducing the content of such harmful compounds produced under stress in plants. Conclusions: This study identified a series of lncRNAs related to the pathways that affect photosynthesis, chlorophyll synthesis, fatty acid synthesis, degradation, and other important effects on drought resistance and oil content. The present study provided a series of lncRNAs for further improvement of crop varieties, especially drought resistant and oil content traits.